2019
DOI: 10.1136/bjsports-2018-100096
|View full text |Cite
|
Sign up to set email alerts
|

Incidence rate and burden of illness at the Pyeongchang 2018 Paralympic Winter Games

Abstract: ObjectiveTo describe the incidence rate (IR) and illness burden (IB) at the Pyeongchang 2018 Paralympic Winter Games.MethodsA total of 567 athletes from 49 countries were monitored for 12 days over the Pyeongchang 2018 Games (6804 athlete days). Illness data were obtained daily from teams with (41 teams, 557 athletes) and teams without (8 teams, 10 athletes) their own medical support, through electronic data capturing systems.ResultsThere were 87 illnesses reported, with an illness IR of 12.8 illnesses per 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
42
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 20 publications
7
42
0
3
Order By: Relevance
“…In the last decade, there has been an increasing focus on the prevention of injuries in sport and also the protection of the health of the athlete. A number of studies have shown that medical illness can be as common as injuries in elite athletes who participate in events and tournaments lasting days to a few weeks, including football,1 2 aquatic sport,3 athletics,4 Summer and Winter Olympic,5 and Paralympic Games 6–9. In all these studies, illnesses most commonly affected the respiratory system, gastrointestinal system, or the skin and subcutaneous tissue, and the most common cause was infection 1–5 10 11…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, there has been an increasing focus on the prevention of injuries in sport and also the protection of the health of the athlete. A number of studies have shown that medical illness can be as common as injuries in elite athletes who participate in events and tournaments lasting days to a few weeks, including football,1 2 aquatic sport,3 athletics,4 Summer and Winter Olympic,5 and Paralympic Games 6–9. In all these studies, illnesses most commonly affected the respiratory system, gastrointestinal system, or the skin and subcutaneous tissue, and the most common cause was infection 1–5 10 11…”
Section: Introductionmentioning
confidence: 99%
“…Trotz der hohen Anzahl an Menschen mit Behinderung und der Größe der Paralympischen Spiele ist die bisher erschienene Literatur zum Thema Hochleistungs-Ski-Alpin mit Behinderung sehr übersichtlich. Mehrfach wurde zuletzt auf einen Mangel an Längsschnittstudien hingewiesen [8][9][10]. Es liegen zwar mehrere Wettkampfbeobachtungen vor [10][11][12][13][14], eine kontinuierliche Evaluation auch des Trainings ist bisher allerdings sehr selten [8].…”
Section: Diskussionunclassified
“…Mehrfach wurde zuletzt auf einen Mangel an Längsschnittstudien hingewiesen [8][9][10]. Es liegen zwar mehrere Wettkampfbeobachtungen vor [10][11][12][13][14], eine kontinuierliche Evaluation auch des Trainings ist bisher allerdings sehr selten [8]. Ein aktuelles Review der Literatur weist weiterhin auf einen Mangel an sportartenspezifischen Untersuchungen hin [9].…”
Section: Diskussionunclassified
“…Curtis and Dillon found that basketball players were the second most injured athletes among wheelchair sports (after track and field). Systematic injury surveillance has been implemented and published for the Summer POG in 2012 and 2016 and the Winter POG in 2018 . Wheelchair basketball was reported to have an injury incidence rate of 12.0 injuries per 1000 athlete‐days (95% CI: 8.3‐16.8) in 2012 and 12.8 injuries per 1000 athlete‐days (95% CI: 9.5‐17.4) in 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Systematic injury surveillance has been implemented and published for the Summer POG in 2012 7 and 2016 8 and the Winter POG in 2018. 9 Wheelchair basketball was reported to have an injury incidence rate of 12.0 injuries per 1000 athlete-days (95% CI: 8.3-16.8) in 2012 and 12.8 injuries per 1000 athlete-days (95% CI: 9.5-17.4) in 2016. More traumatic than overuse injuries were reported from wheelchair basketball during the 2012 POG.…”
mentioning
confidence: 99%